Lost Boy Calculic Adventure (LBCA) Design and Development of Mobile Gamebased Learning for Dyscalculic Children Guided by Universal Design for Learning (UDL) Principles (S/O 21119) - Faisal Mohamed, Nur Fadziana; Annamalai, Subashini (UUM, 2023)
Dyscalculia is a specific learning disability that related to performing mathematic operations with a prevalence of around 3%–7% in the school-aged population. This mathematical disability is a major problem for children to do minor calculations like counting numbers, remembering phone numbers and problem in understanding speed, time, distance etc., which also affects their regular academic activities. A mobile game-based learning application named ‘Lost Boy Calculic Adventure’ (LBCA) which was designed and developed with multimedia elements and the integration of Universal Design Learning (UDL) principles for the use of dyscalculic children aged 5 to 7 years old. This application was intended to be an early intervention to help them learn Mathematics in a motivating way. The purpose of designing and developing the LBCA application is to help the dyscalculic children to improve their numerical. It focuses on numerical topics such as number, money, timed, and aritmetic operations. This report describes the design and development process of the mobile game-based learning application named ‘Lost Boy Calculic Adventure’ (LBCA). It was designed and developed based on the ADDIE (Analysis, Design, Develop, Implement and Evaluate) Model. This research also includes details on the pilot evaluation of the prototype and outlines the findings of the effectiveness evaluation of this mobile application which involved 20 respondents who are dyscalculic children. The ‘Lost Boy Calculic Adventure’ (LBCA) application’s user acceptance was evaluated using the USE (Usefulness, Satisfaction and Ease of Use) Questionnaire (Lund, 2001) which was used to measure its ease of use, ease of learning and satisfaction aspects. The findings described that all of the respondents agreed that the LBCA application is usable and suitable in improving the children numerical skills. This research is an attempt to uphold the obligations of the Department of Social Welfare under the Ministry of Women, Family and Community Development, Ministry of Health and the Ministry of Education to provide recommendations for the care and support of the children with learning disabilities.